2013
DOI: 10.1186/1751-0147-55-11
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the insulin-like growth factor 1 gene is associated with postpartum resumption of ovarian cyclicity in Holstein-Friesian cows under grazing conditions

Abstract: BackgroundInsulin-like growth factor 1 (IGF-1) gene is considered as a promising candidate for the identification of polymorphisms affecting cattle performance. The objectives of the current study were to determine the association of the single nucleotide polymorphism (SNP) IGF-1/SnaBI with fertility, milk production and body condition traits in Holstein-Friesian dairy cows under grazing conditions.MethodsSeventy multiparous cows from a commercial herd were genotyped for the SNP IGF-1/SnaBI. Fertility measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
1
20
0
4
Order By: Relevance
“…The transversion of A→C in the P1 promoter region of bovine IGF1 gene at position 977 bp upstream from the start codon in exon 1 was identified in Polish Holstein Friesian cows and statistically significant differences between individuals of different IGF-1/TasI genotypes were found in milk, fat and protein yield (Szewczuk et al, 2011). Polymorphism in the IGF-1 gene was observed to be associated with postpartum resumption of ovarian cyclicity in Holstein cows (Nicolini et al, 2013). In a genetic polymorphism study of the IGF-I gene, three SNPs were detected in three buffalo breeds of Gujarat (Fatima et al, 2009) and six and five novel polymorphisms in Egyptian water buffalo and Indian buffalo, respectively, in the IGF-1 receptor gene and these SNPs were associated with growth traits (El-Magd et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The transversion of A→C in the P1 promoter region of bovine IGF1 gene at position 977 bp upstream from the start codon in exon 1 was identified in Polish Holstein Friesian cows and statistically significant differences between individuals of different IGF-1/TasI genotypes were found in milk, fat and protein yield (Szewczuk et al, 2011). Polymorphism in the IGF-1 gene was observed to be associated with postpartum resumption of ovarian cyclicity in Holstein cows (Nicolini et al, 2013). In a genetic polymorphism study of the IGF-I gene, three SNPs were detected in three buffalo breeds of Gujarat (Fatima et al, 2009) and six and five novel polymorphisms in Egyptian water buffalo and Indian buffalo, respectively, in the IGF-1 receptor gene and these SNPs were associated with growth traits (El-Magd et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Mullen et al (2011) identified a total of 16 SNPs in IGF-1 and GH gene and its association with milk production, body condition score and fertility traits in Holstein Friesian lactating dairy cows. Szewczuk et al (2011) recorded associations between IGF-1/ TasI polymorphism in Polish Holstein Friesian cows and its association with milk traits and Nicolini et al (2013) polymorphisms in the IGF-1 gene and its association with postpartum resumption of ovarian cyclicity in Holstein cows. Kim et al (2005) identified novel SNPs in the bovine IGFBP-3 gene in Korean cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies showed that plasma IGF‐1 level was increased when plasma insulin was higher (Mackle, Dwyer, & Bauman, ). Although plasma IGF‐1 content was numerically higher in 75SD‐cows than that of 100SD‐animals, the lack of significance could be related with the individual variation, which possibly associated with polymorphism in the IGF‐1 gene of Holstein dairy cows (Nicolini, Carriquiry, & Meikle, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mehmannavaz et al (2010) proved a significant effect of the SNP IGF-1 / Sna BI on estimated breeding values (EBV) for milk production traits in Iranian Holstein bulls, as animals with AB genotype had higher EBV for milk and fat yields than homozygous genotypes. The interval from calving to commencement of luteal activity postpartum (CLA) has been suggested as a suitable selection criteria for fertility, as early CLA is an important factor for a new pregnancy after calving, it presents higher heritability values (16 to 25%) than traditional fertility traits, and it is genetically favorably correlated with traditional fertility traits (Darwash et al , 1997; Petersson et al , 2007; Nicolini et al , 2013). SNPs, 89C/T, 98G/T and 167T/C, of IGF-1 are reported to be significantly associated with milk production and constituent traits in buffaloes (Fatima et al , 2009).…”
Section: Discussionmentioning
confidence: 99%